Estudio de factibilidad técnico-económica para la implementación de transformadores de distribución con aceite vegetal en redes eléctricas situadas en climas cálidos. (2020)
New requirements for a better sustainable energy policy around the world are easy to observe, many projects in sustainable energy are developed wherein the academia works together the authorities and commercial firms such as electrical grid utilities. Companies in the energy sector, mainly those in the electricity sector, are working on the implementation of new technologies and strategies to reduce their impact on the environment due to the large areas they cover. One of the main assets are local distribution transformers, these equipment use insulating and refrigerant medium mineral oil, these oils have a negative impact on the environment due to their chemical properties, for this reason one of the suggested solutions is to replace mineral oil by fluids based on natural esters, also known as vegetable oils, which provide better technical and environmental properties compared to mineral oils, making it a safe substitute for mineral oil. Natural esters are based on clean technologies in order to guarantee the proper behavior and operation of transformation equipment. The main goal of the present paper is to present a technical-economic analysis obtained from five years of applications of oil-immersed transformers using natural ester fluids in Colombia. The methodology considers forty-four oil-immersed distribution Transformers, a half use mineral oil and the other side use natural ester, operating under the same load regime. Results evidenced the feasibility of implementing this technology because the costs are very similar, and the reduction of risks and environmental impact is considerable.